Semantic processing in the left inferior prefrontal cortex: a combined functional magnetic resonance imaging and transcranial magnetic stimulation study. - Devlin, J; Matthews, P; Rushworth, M (2003)
The involvement of the left inferior prefrontal cortex (LIPC) in phonological processing is well established from both lesion-deficit studies with neurological patients and functional neuroimaging studies of normals. Its involvement in semantic processing, on the other hand, is less clear. Although many imaging studies have demonstrated LIPC activation during semantic tasks, this may be due to implicit phonological processing. This article presents two experiments investigating semantic functions in the LIPC. Results from a functional magnetic resonance imaging experiment demonstrated that both semantic and phonological processing activated a common set of areas within this region. In addition, there was a reliable increase in activation for semantic relative to phonological decisions in the anterior LIPC while the opposite comparison (phonological vs. semantic decisions) revealed an area of enhanced activation within the posterior LIPC. A second experiment used transcranial magnetic stimulation (TMS) to temporarily interfere with neural information processing in the anterior portion of the LIPC to determine whether this region was essential for normal semantic performance. Both repetitive and single pulse TMS significantly slowed subjects' reactions for the semantic but not for the perceptual control task. Our results clarify the functional anatomy of the LIPC by demonstrating that anterior and posterior regions contribute to both semantic and phonological processing, albeit to different extents. In addition, the findings go beyond simply establishing a correlation between semantic processing and activation in the LIPC and demonstrate that a transient disruption of processing selectively interfered with semantic processing.